RELEVANCE OF BILINGUALISM IN ADULT LEARNERS’ ENGLISH LANGUAGE DEVELOPMENT IN SOUTH-WEST NIGERIA - Chris Ajibade Adetuyi (Journal of English Education, 2019)
The general English studies was introduced as a compulsory course for sandwich learners of colleges of education with a view to allowing them attain proficiency in English. Despite the measure, it seems attainment of proficiency is a mirage. Unattainment of English proficiency in sandwich program has been ascribed to less satisfactory teaching skill embracing language competence and pedagogy. However, there has been a dearth of studies on the teaching method of facilitators of the course. This paper therefore, has a focus on the relevance of bilingualism, in English Language development in the sandwich centers. Pretest and posttest control group as quasi-experimental design with 3X2X2 factorial matrix was adopted for the study. Data were analyzed using analysis of covariance and multiple classification analysis. Bilingual method of teaching was ascertained as having an upper hand over Direct and conventional method with a mean score of 67.54. Bilingualism therefore proved relevant to the teaching of General English Studies to the Adult learners. The paper concludes that facilitators should recognize the learners' mother tongue in the learning of English. This would stimulate learners' interest, accelerate their understanding, and ensure effective class-contact needed in adult education teaching-learning process.